ПИТАННЯ ДІАГНОСТИКИ УПРАВЛІНСЬКИХ РІШЕНЬ В ТЕРИТОРІАЛЬНИХ ГРОМАДАХ РІЗНИХ РЕГІОНІВ УКРАЇНИ - Vuychenko, Maryna; Sklyaruk, Nazar (Zhytomyr Ivan Franko State University, 2025)
The article considers the current problems of social diagnostics of management decisions in the conditions of the Russian-Ukrainian war, which has been going on for three years. The main regulatory documents that regulate the forms and content of management during the war, the real state of the effectiveness of management decisions, social criteria for the implementation of management decisions in the political, economic, social, military spheres of society are analyzed. Possible ways to solve these problems are proposed. Modern methods of social diagnostics, principles of building social forecasting and planning are characterized. The article notes that our whole life is connected with a certain choice of conditions of existence in society, the solution of large and small problems of a personal and social nature that require making some decisions. This can be a place of residence, education and choice of profession, family and raising children, sports and recreation, friendship and enmity, etc. All this requires making a decision that will have both positive and negative consequences, can be personal or have a social character. When exercising managerial influence on the activities of territorial communities, an important issue is the diagnosis of the specific environment in which they function. An equally important factor is the assessment of the personal competencies of those subjects of managerial activity who directly exercise this managerial influence. Social practice has led to the emergence of people who have the right and opportunity to manage other people, to decide the fate of other people, classes and ethnic groups, even entire countries and peoples. This is a large social group of managers. Sometimes the term “management” is used for them. In the current extremely complex conditions caused by the war, careful attention to the competence and effectiveness of each managerial decision is extremely important not only at the state level, but also at the level of each individual territorial community. Therefore, the study of the problem of diagnosing managerial decisions at all levels becomes particularly relevant.